DATSURYOKU: designing environment–body interaction for implicit muscle relief*. (1st February 2022) - Murai, Akihiko; Washino, Sohei; Mochimaru, Masaaki
Abstract : Decreased daily activities and tension frequently cause excessive muscle co-contractions implicitly, resulting in decreased performance and injury in sports. In this study, we modify the interaction between the environment and human body freely and temporarily, using environmental kinodynamic intervention. We target the load reduction during walking, which is realized by walking on a treadmill, where the acceleration/deceleration of the treadmill acts as the intervention. A forward dynamics simulation using a kinodynamic body model is used to design the intervention pattern. The designed intervention pattern is implemented in a real environment for verification, using a subject experiment with six subjects. The results demonstrate that the vertical component of the ground reaction force decreases by 2.14% and gastrocnemius and tibialis anterior activities decrease by 1.89% and 7.08 E − 01 % when the treadmill speed is low at heel contact and accelerates gradually. Hence, we conclude that the intervention decreases the change in the muscle length during walking, suppresses the stretch reflex, and reduces muscle activity. These results demonstrate the possibility to modify human motor control systems using non-invasive kinodynamic interventions, thereby realizing implicit muscle relief (DATSURYOKU) in sports and daily life, as well as to prevent their injuries. GRAPHICAL ABSTRACT: UF0001